The Role of Family Counseling in Improving Adolescents’ Mental Health - Tiara Agustine; Azni Nurul Fauzia; Andrew Kyaw (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Adolescents are particularly vulnerable to mental health problems due to rapid biological, psychological, and social changes. Addressing these issues requires effective and systemic interventions, one of which is family counseling. Objective: This study aims to review the role and effectiveness of family counseling in improving adolescent mental health. Method: A systematic literature review (SLR) method was used to analyze relevant studies and provide a comprehensive understanding applicable to clinical and policy settings. Results: The findings reveal that family counseling is effective in treating anxiety, depression (including Major Depressive Disorder), eating disorders such as anorexia nervosa, internet gaming disorder, suicidal ideation, and self-harm behaviors. It also enhances parental support, improves communication and relationships within families, strengthens family functioning, and fosters a healthier home environment. Furthermore, it supports better emotional regulation, adaptability, positive coping strategies, and school adjustment in adolescents. Conclusion: Family counseling offers a holistic approach to adolescent mental health. Contribution: This study contributes theoretically and practically to the understanding of family-based mental health interventions for youth.